Solving the stability problem of vertical slope according to the effective stress field - Do, Thang (2020)
The deformation of soil as well as its shear strength depends on the effective stress. In this paper, a new direct method has been developed to determine the effective stress field in soil based on the shear potential. The method allows solving the stability problem of vertical slope.